FRI0349 Is interspinous bursitis the explanation of cervical and lumbar pain in polymyalgia rheumatica? a study with fdg-pet/ct. (23rd January 2014) - Camellino, D.; Morbelli, S.; Paparo, F.; Massollo, M.; Sambuceti, G.; Cutolo, M.; Cimmino, M. A.
Abstract : Background: Polymyalgia rheumatica (PMR) is a common inflammatory disease of the elderly characterized by girdle pain and cervical and lumbar aching. Interspinous bursitis has been suggested as potential cause of the symptoms at the lumbar spine level in a study performed with MRI (1 ). In rheumatology, 18F-fluorodeoxyglucose (FDG) positron emission tomography integrated with computed tomography (PET/CT) is used mainly for the demonstration of large-vessel vasculitis. Characteristic uptake patterns are also seen in PMR, where bursal and joint involvement is highlighted in shoulders, hips, column, and ischium (2 ). Objectives: To evaluate the spine structures involved in PMR by FDG-PET/CT in a cohort of consecutive, untreated patients. Methods: Sixty-five consecutive patients (44 women, median age 73 years, range 50-87 years), fulfilling Bird's criteria for PMR were studied. After a standardized physical exam, which included pain and tenderness of the spine, they underwent simultaneous FDG-PET and CT imaging from the skull base to the knee using an integrated PET/CT scanner (Hirez; Siemens Medical Solutions, Knoxville TN, USA), after injection of 4.8-5.2 MBq of F18-FDG per kg body weight. FDG-uptake was scored according to liver uptake as 0=no uptake present, 1=lower than liver uptake, 2=similar to liver uptake, 3=higher than liver uptake. These values were further subdivided into "positive" (scores 2 and 3) and "negative" (scores 0 and 1). Sites of pathological uptake in the column were recorded. Results: Table 1 shows the clinical and PET/CT results. FDG uptake was more frequent in the lumbar spine than in the other locations, and in the cervical than in the dorsal spine (p<0.0001). The corresponding score was higher in the lumbar than in the cervical spine (1.3±1.2 vs 0.3±0.8, p<0.0001). Uptake was almost always present in a single spinal bursa, comprised between the 3 rd and 6 th cervical vertebrae and between the 4 th and 5 th lumbar vertebrae. Spontaneous pain was more frequent in the cervical and lumbar spine than in the dorsal spine (p<0.02). No correlation was found between uptake and spontaneous or provoked pain. There was an association between cervical and lumbar bursitis (r=0.34, p=0.007). Conclusions: Interspinous bursitis is a frequent finding in the lumbar spine of patients with PMR. It is however not associated with the presence of clinical symptoms and can hardly explain the spinal pain reported by the patients. Cervical pain is more frequent than lumbar pain in PMR patients and might be caused by shoulder girdle involvement. References: Salvarani C, Barozzi L, Cantini F, Niccoli L, Boiardi L, Valentini M, et al. Cervical interspinous bursitis in active polymyalgia rheumatica. Ann Rheum Dis 2008;67:758–61. Camellino D, Cimmino MA. Imaging of polymyalgia rheumatica: indications on its pathogenesis, diagnosis and prognosis. Rheumatology (Oxford) 2012; 51: 77-86. Disclosure of Interest : None Declared